Briefing on the Accounting Cycle as a Basis for Preparing Financial Statements for Providentia High School Students - Yanti Yanti; Kelvin Kelvin (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2025)
Provision for early accounting learning will be an important foundation in forming financial literacy skills for students. This paper aims to provide an understanding of the accounting cycle from beginning to end as a basis for preparing financial reports for SMA Providentia. This community service (PKM) activity is carried out using three methods, namely: (1) Explanation of the theory given in the form of a Module, (2) Using an approach based on Practice Questions and Group Discussions, and (3) Using a Games approach in groups as a form of feedback. This PKM activity was carried out on April 24, 2025, at 10.00 a.m onsite. The training was attended by 19 grade 12 students. The training was divided into 3 sessions. In general, the results of this PKM activity were quite successful in providing basic knowledge regarding the accounting cycle. This can be seen from the discussion of questions and quizzes given to participants who did not previously understand the accounting cycle. From the results of interviews conducted by the team with participants, they stated that they were satisfied with the delivery of the material provided.